Comparative evaluation of the new xTAG GPP multiplex assay in the laboratory diagnosis of acute gastroenteritis. Clinical assessment and potential application from a multicentre Italian study. (May 2015) - Vocale, C.; Rimoldi, S.G.; Pagani, C.; Grande, R.; Pedna, F.; Arghittu, M.; Lunghi, G.; Maraschini, A.; Gismondo, M.R.; Landini, M.P.; Torresani, E.; Topin, F.; et al.
Highlights: Improving the diagnostic system would decrease hospitalization costs. The mechanism explains the full reversibility of the diagnosis of diarrhoea. Using the GPP assay, we will be able to identify undiagnosed infections as well as co-infections. Summary: Objective: Gastroenteritis caused by a single pathogen or multiple pathogens remains a major diagnostic challenge for the laboratory. The treatment of diarrhoea is based on microbiological results. Diagnosis is achieved using different laboratory techniques that have variable sensitivity and specificity. xTAG GPP is a new multiplex PCR assay that simultaneously detects 15 different pathogens responsible for diarrhoea. The results of the first multicentre study in Italy to evaluate the potential clinical application of the GPP assay in the laboratory diagnosis of diarrhoea are reported here. Methods: Faeces specimens ( N = 664) from hospitalized patients were tested with the GPP assay using a Luminex 200 instrument. All specimens were run using comparator methods following a routine algorithm: culture for bacteria, enzyme immunoassay and PCR for viruses, and microscopy for parasites. Results: Of the samples tested with the GPP, 53.61% (356/664) gave positive results, as compared to 45.33% by routine testing. Of the positive specimens, 34.55% showed the presence of genomic DNA from multiple pathogens. The Luminex method showed an increase in the percentage of positivity of 8.28%. Conclusions: The GPP assay can be considered a helpful tool for the detection of gastrointestinal pathogens, with a hands-on time of 5 h; it provides accurate data for the clinical management of hospitalized patients and for epidemiological surveillance.